Total thyroidectomy alone versus ipsilateral versus bilateral prophylactic central neck dissection in clinically node-negative differentiated thyroid carcinoma. A retrospective multicenter study. Issue 1 (January 2017) - Calò, P.G.; Conzo, G.; Raffaelli, M.; Medas, F.; Gambardella, C.; De Crea, C.; Gordini, L.; Patrone, R.; Sessa, L.; Erdas, E.; Tartaglia, E.; Lombardi, C.P.
Abstract: Background: Central neck dissection (CND) remains controversial in clinically node-negative differentiated thyroid carcinoma (DTC) patients. The aim of this multicenter retrospective study was to determine the rate of central neck metastases, the morbidity and the rate of recurrence in patients treated with total thyroidectomy (TT) alone or in combination with bilateral or ipsilateral CND. Methods: The clinical records of 163 clinically node-negative consecutive DTC patients treated between January 2008 and December 2010 in three endocrine surgery referral units were retrospectively evaluated. The patients were divided into three groups: patients who had undergone TT alone (group A), TT with ipsilateral CND (group B), and TT with bilateral CND (group C). Results: The respective incidences of transient hypoparathyroidism and unilateral recurrent nerve injury were 12.6% and 1% in group A, 23.3% and 3.3% in B, and 36.7% and 0% in C. Node metastases were observed in 8.7% in group A, 23.3% in B, and 63.3% in C. Locoregional recurrence was observed in 3.9% of patients in group A and in 0% in B and C. Conclusions: We found no statistically significant differences in the rates of locoregional recurrence between the three groups. Therefore, TT appears to be an adequate treatment for these patients; CND is associated with higher rates of transient hypoparathyroidism and cannot be considered the treatment of choice even if it could help for more appropriate selection of patients for RAI. Ipsilateral CND could be an interesting option considering the lower rate of hypocalcemia to be validated by further studies.